Interrogations in Philippine cultural history the Ateneo de Manila lectures - Mojares, Resil B. (Ateneo De Manila University Press, 2017)
These articles interrogate diverse issues in Philippine cultural history: the place of Nick Joaquin in the nation's historiography; the debate on the class position of Andres Bonifacio and the revolutionary outbreak of 1896; the state of regional literary studies and the case of Filipino crime fiction; and Philippine electoral politics as seen in the cracked mirror of Pascual Racuyal's career. The book ends with the author's reflections on the past four decades of Philippine cultural studies.